A Review: Application of Deep Learning in Smart City Analysis - Phuong Dong (International Journal of Smart Systems, 2023)
The rapid development of smart cities has led to the increasing demand for advanced technologies that can effectively manage the vast amount of data generated by various sources. Deep learning, a subset of machine learning, has been successfully applied in various domains and has shown remarkable performance in analyzing large-scale and complex data. This review paper presents a comprehensive analysis of the recent advancements and applications of deep learning in smart city analysis. The paper covers the different use cases of deep learning in the smart city domain, such as transportation, energy, healthcare, security, and public services. The review also highlights the challenges and opportunities of applying deep learning in the smart city domain and suggests potential research directions for future work. The analysis demonstrates the effectiveness of deep learning in smart city analysis and its potential to contribute to the development of smarter and more sustainable cities.